ADMINISTRASI PEMBIAYAAN PENDIDIKAN DI MIS NURUL HIDAYAH KECAMATAN MEDAN DENAI - Hemi wulandari; Putri Siregar, Suhaila; Silvia, Bella (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
The purpose of this observation is to explain how Education Funding Administration at the Elementary School level is carried out at MIS Nurul Hidayah, Medan Denai District. This observation is included in a descriptive study with a qualitative approach. Data was collected through interviews, observations, and documentation. The validity of the data was tested through triangulation techniques and sources. Data were analyzed using Miles Huberman’s interactive model. The results of observations show that the sources of education funding at MIS Nurul Hidayah Medan Denai consist of student parents’ contributions, Central BOS/Regular BOS, and assistance from foundations. These funds are used to fulfill National Education Standards, including Graduate Competency Standards, Content Standards, Process Standards, Facilities and Infrastructure Standards, Management Standards, Education Financing Standards, and Educational Assessment Standards, except for Educator and Education Personnel Standards. However, there is a discrepancy between the budget stated in the Activity Plan and School Budget (RKAS) and the results achieved. This is due to limited funds received from the government and the small number of students.